Patterns of recurrence amongst patients undergoing resection of oral squamous cell carcinoma with curative intent. Issue 10 (December 2022) - Zubair, Farhan; Farooq, Saadia; Wright, Sylvia; Schipani, Stefano; McMahon, Jeremy
Abstract: This study was aimed to identify key clinicopathological variables that predict recurrence in those undergoing curative resection of oral squamous cell carcinoma (OSCC) with emphasis on initial treatment failure patterns. Between February 2006 to May 2020, clinicopathological data on 833 patients who underwent curative resection of OSCC were gathered. Outcomes of interest included local, regional, distant, and overall recurrence. Univariate analysis was performed to identify significant clinicopathological variables for each recurrence type, and a multivariate regression analysis was utilised to generate predictive models. A total of 187 patients (22.4%) developed recurrent disease; 79 local, 63 regional, and 46 distant. For local recurrence: tumour depth of invasion (DOI) >5-–10 mm, tumour DOI >10 mm and modified Glasgow Prognostic Score (mGPS) 2 were independently predictive (c-index 0.708). For regional recurrence: primary OSCC of hard palate/maxilla, pN1, pN3b, and non-cohesive invasive front were independently predictive (c-index 0.738). For distant recurrence: pN1 pN2a, pN2b, pN2c, pN3b, and tumour DOI >10 mm were independently predictive (c-index 0.809). For recurrence at any site; pN1, pN2a, pN2b, pN2c, pN3b, tumour DOI >5–10 mm, tumour DOI >10 mm, mGPS 2, and involved surgical margins were independently predictive (c-index 0.750). Recurrence events after curative treatment for OSCC are relatively predictable on the basis of available clinicopathological characteristics. It seems likely that trials of adjuvant systemic therapy in high-risk OSCC will continue to be designed with emerging therapeutic agents. Trials should focus on those of highest risk of relapse and this study adds clarity to the selection of the correct target population.